A Comprehensive Analysis Of Visual Communication Design And Symbolic Meaning In The Documentary 'The Painting Of Life Vincent Van Gogh - Daniartha, Anak Agung Gede (Journal of Visual Art and Design Studies: Les-Guet's, 2025)
This study analyzes visual representation in a documentary video about Vincent van Gogh through the lens of deconstructionist semiotics and visual communication design principles, with particular focus on the application of Dadaist style and experimental typography. The research is motivated by the crucial role of design consistency in effectively conveying symbolic messages through visual media. Employing qualitative methods, the study examines characteristic Dadaist elements such as collage, random image fragments, and unconventional typography in expressing a narrative of rebellion. Findings indicate that the opening bumper successfully creates a "rebel" impression through deliberately chaotic visual composition, while stylistic inconsistencies in the credit titles diminish overall visual integrity. The study concludes by emphasizing the importance of harmonious integration between Dadaist aesthetics and narrative messaging to achieve effective and meaningful visual communication design.